Pelatihan Fotografi dan Editing untuk Meningkatkan Promosi Produk Kerajinan Rajut - Imanuel Madea Sakti; Dinita Christy Pratiwi; Setia Candra Jati (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2022)
In the era of technology and information (IT) development and the adoption of the internet nowadays, promotion activities, especially digital marketing, have become the main necessity for a business. However, some people have problems providing attractive marketing content for promotions. One of the fundamental issues is the basic ability to take photos and make simple editing. Even though at this time, most people have access to mobile devices (smartphones) that can support the promotion activities. For example, a smartphone's photo camera can produce high-resolution photos and a design app on a smartphone can be used to edit photos for free. This community service activity was a collaboration between CEMSED FEB UKSW and Komunitas Bermain Benang. This community consists of mothers who have a hobby of knitting. By participating in this activity, participants are expected to have the simple photo and editing skills to enhance the promotion of knitting craft products.